Healthcare utilization associated with adherence to antibiotics for abdominal surgeries in Japan: cross-sectional analysis of administrative database. (22nd January 2021) - Imai, Shinobu; Kiyomi, Anna; Sugiura, Munetoshi; Fushimi, Kiyohide
Abstract: Background: Since patients receiving surgery may experience surgical site infections, therapeutic guidelines for reducing hospitalization time and cost include appropriate antibiotic use. However, the association between adherence to therapeutic guidelines and healthcare utilization is currently unclear. Objectives: This study aimed to confirm the positive association between the adherence to guidelines of antibiotic therapy and a reduction in the length of stay and cost of hospitalization, especially considering the high infection rates in abdominal surgery. Methods: This cross-sectional study used administrative data (diagnosis procedure combination data) collected using the case-mix system implemented in acute-care hospitals in Japan. We assessed the length of hospital stay and cost of hospitalization for patients who received prophylactic antibiotic for abdominal surgeries consistent with therapeutic guidelines. The data of patients aged 15 years or older who received appendectomy, laparoscopic cholecystectomy or inguinal hernia repair were extracted. The appropriateness of antibiotic prophylaxis was evaluated in terms of the Japanese guidelines for antibiotic selection and treatment duration. To assess the mean difference in antibiotic costs and length of stay, we performed the propensity score matching by confounding factors. Furthermore, we assessed the progress in healthcare utilization of this therapy over a decade. Results: Of the 302 233 patients who received single general surgery from April 2014 to March 2016, 198 885 were eligible for analysis after applying the exclusion criteria (143 975 in the adherence and 54 910 in the non-adherence group). Each group comprised 48 439 patients after propensity score matching. Inappropriate antibiotic selection and duration were observed in 9294 (9.8%) and 687 (0.7%) of inguinal hernia repairs, 6431 (25.3%) and 311 (1.2%) of appendectomies and 38 134 (48.5%) and 391 (0.5%) of laparoscopic cholecystectomy cases, respectively. After propensity score matching by operation type, average hospitalization length (6.5 [SD 3.8] and 7.3 [SD 4.8] days) and costs (536 000 [SD 167 000] JPY and 573 000 [SD 213 000] JPY) differed significantly between adherence and non-adherence groups. Conclusion: The results revealed that unnecessary healthcare utilization was associated with failure to adhere to therapeutic guidelines for prophylactic antibiotic therapy in elective general surgeries. We concluded that the progress of reduction in length of hospitalization over the decade was successful. Notably, adherence to treatment duration was better than that was 10 years ago. In this decade, administrators in hospitals have attempted to reduce the duration of hospitalization by developing various clinical pathways for surgical procedures and quality indicators. However, 15 877 patients (8.7%) were prescribed oral antibiotics the day after surgery. These observations should be evaluated further.